Desprendimiento de rutina de Pablo Aranda: homenaje al Quijote y parodia de la novela policíaca - Camacho-Platero, Luzmila (El Colegio de México, 2025)
The purpose of this paper is to analyze some of the constituent elements of Desprendimiento de rutina, a short novel by Pablo Aranda Ruiz whose originality lies in using literary pastiche to develop a tangled plot exhibiting a society in crisis. Through the detailed reading of the text and the study of its narrative structure, I suggest that Aranda resorts to parody and the genre of the psychological novel to create a work sprinkled with elements of criminal fiction, Don Quixote and mass culture, and that with these elements he creates an antihero incapable of distinguishing between truth and lies, between reality and fantasy.